Evaluasi Indeks Tarik dan Indeks Sobek pada Bleaching Pulp: Pengaruh Hidrogen Peroksida (H2O2), Klorin Dioksida (ClO2) dan Suhu - Ulia, Hasnah; Nurmalasari, Enny; Yahya, Agung Kurnia; Rahayu, Puji (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Indonesia is one of the leading Pulp and paper producers globally, with an estimated annual growth rate of 3.5%. However, domestic production has not yet fully met the domestic needs and export demand for paper. Currently, hydrogen peroxide (H2O2) and chlorine dioxide (ClO2) are the primary bleaching agents used in Pulp and paper production. This research aims to evaluate the effects of H2O2, ClO2, and temperature on product quality parameters, specifically the tensile and tear indices. The variations of ClO2 used are 2%, 0.4%, and 0.7%; H2O2 concentrations are 0.1%, 0.2%, and 0.4%; and the temperatures used are 75°C and 85°C. The study found that the addition of ClO2 at a concentration of 0.7% resulted in the highest tensile index of 76.9 N.m/g and a tear index of 3.5 m.N.m²/g. The addition of H2O2 at a concentration of 0.1% resulted in a tensile index of 83.9 N.m/g and a tear index of 9.4 m.N.m²/g. Temperature variations did not significantly affect the tensile and tear indices, with the tensile index reaching 9.35 m.N.m²/g. The addition of H2O2 is essential as it enhances the bleaching process and improves the mechanical properties of the Pulp, which is beneficial for optimizing bleaching conditions to enhance product quality, thus meeting both domestic needs and export demands